2013
DOI: 10.1109/tvt.2013.2263156
|View full text |Cite
|
Sign up to set email alerts
|

Control Design of Variable-Geometry Suspension Considering the Construction System

Abstract: The paper proposes a method in which the construction of a variable-geometry suspension and the design of a robust suspension control are performed simultaneously in order to enhance vehicle stability. The control system guarantees various crucial performances which are related to the chassis roll angle and half-track change.Moreover, by changing the camber angles of the front wheels the yaw rate of the vehicle is modified, which can be used to reduce the tracking error from the reference yaw rate. The design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Thus, the effect of wheel tilting can be neglected. In spite of the reachable set analysis, Németh and Gáspár [2013a] proposes that the modification of the wheel camber angle has a significant advantage in vehicle control. Thus, in this example the efficiency of the variable-geometry suspension in vehicle dynamics is not handled adequately by the linear analysis.…”
Section: Motivation Examplementioning
confidence: 99%
“…Thus, the effect of wheel tilting can be neglected. In spite of the reachable set analysis, Németh and Gáspár [2013a] proposes that the modification of the wheel camber angle has a significant advantage in vehicle control. Thus, in this example the efficiency of the variable-geometry suspension in vehicle dynamics is not handled adequately by the linear analysis.…”
Section: Motivation Examplementioning
confidence: 99%
“…Many efforts have been made to alter the camber in order to address this issue. 38 The research shows that camber control can improve vehicle stability, safety, and manoeuvrability in general while having some disadvantages. First, although motivated by using camber to maximise the tyre’s lateral force, most of the research ended up with improving the vehicle performance in the range where the side-slip force is far from saturation.…”
Section: Introductionmentioning
confidence: 99%
“…First, although motivated by using camber to maximise the tyre’s lateral force, most of the research ended up with improving the vehicle performance in the range where the side-slip force is far from saturation. 3–5,8 In that range the side-slip force can still do the job well; and hence, controlling camber may not be as effective as that of steering angle. The second downside is that the controlled camber mechanism compromises with changing the suspension geometry such as roll centre, 3,4 which may badly affect vehicle dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the effects of adaptive fuzzy logic control (AFLC) on vehicle dynamics, Baghaeian and Akbari compared AFLC and proportional-integral-derivative (PID) in VGS and showed that AFLC has improved parameters of stability [26]. Nemeth and Gaspar [27] propose a method in which the structure of a variable geometry suspension system and the design of a robust control are achieved simultaneously in order to improve vehicle stability. Also, Gaspar analyzed the efficiency of the variable geometry suspension in preliminary works in the coordination of steering and wheel tilting [28].…”
Section: Introductionmentioning
confidence: 99%